The East Island Retention of Health Professionals Project – English, An Asset! : REISA Internships - A Success Story - Gatre Guemiri, Fatiha; Zappitelli, Juliana; Mirtaheri, Mina; Granner, Francine; Hendrickson-Nelson, Mary (2015)

Workforce of Tomorrow Youth Skills Link Project - Buckle, Heidi (Coasters Association, 2015)
The Coasters Association implemented a fourth phase of the Youth Skills Link Project which began on May 18th, 2015, and ran until November 13th, 2015, funded by Service Canada. The YSLP entitled: “Workforce of Tomorrow” was designed to help out eight (8) youth between the ages of 15-30 throughout the Lower North Shore, to overcome employment barriers by enabling them to develop/improve on self-knowledge, employability skills, skills enhancement, through three weeks of Group Based Employability Skills training, and seventeen (17) weeks of work experience. The project was posted throughout the coast inviting youth to take part in the project based out of their respective communities/municipalities. A total of seven (7) applicants were received, interviews were carried out with each applicant and job placement was necessary before final selection. The selected youth derived from the Municipalities of C te Nord du Golfe du Saint Laurent, Gros Mecatina, Bonne Esperance, and Blanc Sablon were hired for twenty (20) weeks of training and work experience.

African-Canadian Career Excellence : 2015 Employer Survey - Community Economic Development and Employability Corporation (CEDEC) (2015)
This report provides the final data analysis and interpretation of the 2015 employer survey on the hiring norms and practices of businesses across various sectors and industries in the Greater Montreal area, with a focus on employers’ attitudes towards the importance of a having a diverse workforce. This study is part of the African-Canadian Career Excellence (ACCE) initiative aimed at countering the migration of Black graduates from Montreal.

African-Canadian Career Excellence : 2014 Student Survey : The Needs and Challenges of Education Black Youth in Obtaining Meaningful and Sustainable Employment - Community Economic Development and Employability Corporation (CEDEC) (2015)

Initiative pour l'excellence de la carrière des Afro-Canadiens : Enquête réalisée en 2014 : Les besoins et les défis auxquels font face les jeunes de race noire pour obtenir un emploi rémunérateur et durable - Community Economic Development and Employability Corporation (CEDEC) (2015)
Ce rapport présente l’analyse et l’interprétation de l’enquête réalisée auprès des étudiants du premier cycle universitaire en 2014 sur leurs perceptions de la transition vers l’emploi à Montréal. Ce résumé, une étape réalisée par l’Initiative pour l’Excellence de la carrière des Afro-Canadiens œuvrant à contrer la migration des jeunes diplômés noir montréalais, vise à influencer la conception de formations s’adressant aux jeunes diplômés afin de faciliter le lancement de leur carrière et la progression de celle-ci au Québec.

Youth Development Initiatives - Coasters Association (2015)
The Coasters Association has had many achievements over the years regarding youth initiatives, and priority areas have been identified. These achievements have contributed to the development and vitality of the region’s communities; however, there are many challenges that remain to hinder the future development and sustainability of the region.

Building a Career as an Artist - Macdonald, Amy; Shaughnessy, Kyra (2015)